Integrated battery thermal management and CO2 control in electric buses using recirculated air and waste heat recovery - Min Gyu Choi; Mahdi Koushaeian; Abdullah; Jun Su Park; Hwa Yeong Lee; Jinyoung Chang; Jae Dong Chung (Results in Engineering, 2024)
In recent years, electric vehicles (EVs) have significantly progressed due to their environmental protection and energy-saving advantages. However, maintaining indoor thermal comfort and effective battery thermal management are critical considerations for EVs. Unlike conventional vehicles, EVs cannot use waste heat and depend on heat pump systems for winter heating and summer cooling. This research proposes a novel system to reduce the energy consumption of heat pump systems by using recirculated air while addressing the challenges of battery temperature management and maintaining safe CO2 concentrations in the cabin. The primary objectives of this research are threefold: first, to ensure passenger comfort through an integrated approach that includes cabin CO2 concentration safety; second, to recover heat from recirculated cabin air to save energy and control battery temperature; and third, to comprehensively analyze the performance of the Electric Vehicle Thermal Management System (EVTMS) using precise Computational Fluid Dynamics (CFD) analysis and mathematical modeling. This study will significantly enhance the understanding of energy consumption related to CO2 concentration control; an aspect previously overlooked in the literature. It will develop a battery temperature management strategy that leverages bus exhaust heat. These contributions will aid in achieving both passenger comfort and battery stability in electric buses, providing practical insights for the design and optimization of thermal management systems for future electric buses.